Telephone-based low intensity therapy after crisis presentations to the emergency department is associated with improved outcomes. (October 2015) - Bidargaddi, Niranjan; Bastiampillai, Tarun; Allison, Stephen; Jones, Gabrielle M; Furber, Gareth; Battersby, Malcolm; Richards, David
Introduction: In Australia there is an overwhelming need to provide effective treatment to patients presenting to the Emergency Department (ED) in mental health crisis. We adapted Improving Access to Psychological Therapies service model (IAPT) from the National Health Service (NHS) method for the large scale delivery of psychological therapies throughout the United Kingdom to an Australian ED setting. This telephone-based low intensity therapy was provided to people presenting in crisis to the EDs with combinations of anxiety, depression, substance use, and suicidal thinking. Methods: This uncontrolled study utilised session-by-session, before-and-after measures of anxiety and depression via Patient Health Questionnaire (PHQ-9) and Generalised Anxiety Disorder-7 (GAD-7). Results: Of 347 eligible post-crisis ED referred patients, 291 (83.9%) engaged with the IAPT team. Most patients (65%) had attended the ED previously on an average of 3.9 (SD = 6.0) occasions. Two hundred and forty one patients received an average of 4.1 (SD = 2.3) contacts of low-intensity psychological therapies including 1.2 (SD = 1.7) community outreach visits between 20th Oct 2011 and 31st Dec 2012. Treated patients reported clinically significant improvements in anxiety, depression and suicidal ideation. Uncontrolled effect sizes were moderate for anxiety (0.6) and depression (0.6). Discussion: The Australian ED IAPT program demonstrated that the UK IAPT program could be adapted for emergency mental health patients and be associated with similar clinical benefits as the original program. Funding: The Flinders Medical Centre IAPT program received Emergency Department project funding from the Australian Commonwealth Government through the Council of Australian Governments (COAG) and the South Australian Government initiative, Every Patient Every Service (EPES).